The magic faraway tree - Blyton, Enid (Egmont UK Ltd.: United Kingdom, 2014)
"The Magic Faraway Tree" is the second story in the "Faraway Tree" series by the world's best-loved children's author, Enid Blyton. When Joe, Beth and Frannie move to a new home, an Enchanted Wood is on their doorstep. And when they discover the Faraway Tree, it proves to be the beginning of many magical adventures! Join them and their friends Moonface, Saucepan Man and Silky the fairy as they discover which new land is at the top of the Faraway Tree. Will it be the Land of Spells, the Land of Treats, or the Land of Do-As-You-Please? Come on an amazing adventure - there'll be adventures waiting whatever happens. Enid Blyton's funny, magical adventure stories have become true classics, loved by millions and still selling thousands of copies every year.
Keywords: English, Fiction